Resource allocation and planning for program management - Vaziri, Kabeh; Nozick, Linda K.; Turnquist, Mark A. (2005 Winter Simulation, 2005)
Much of the project scheduling literature treats task durations as deterministic. In reality, however, task durations are subject to considerable uncertainty and that uncertainty can be influenced by the resources assigned. The purpose of this paper is to provide the means for program managers (who may have responsibility for multiple projects) to optimally allocate resources from common resource pools to individual tasks on several competing projects. Instead of the traditional use of schedules, we develop control policies in the form of planned resource allocation to tasks that capture the uncertainty associated with task durations and the impact of resource allocation on those durations. We develop a solution procedure for the model and illustrate the ideas in an example.